Financial performance measures for Kansas beef cow farms - Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Financial performance measures assist managers in making strategic plans and tracking progress in relationship to a farm’s goals. Kansas Farm Management Association data were used to compute average financial performance measures by herd size for beef cow farms. Farms with over 200 cows derived a larger percent of their income from beef cow production, tended to be large r in terms of gross farm income and total assets, were more profitable, and had lower debt ratios. Differences in financial performance among beef cow farms suggest that comparisons should be made only with herds that are similar in size.
Keywords: Beef; Profitability; Liquidity; Solvency; Financial efficiency; Cows